Serum electrolyte levels and their association with edema severity in pediatric edematous malnutrition - Uddin, Mohammad Nasir; Sultana, Farhana; Rahman, Mohammad Mizanoor; Manik, Zamil Ahmed; Ahmed, Ifthakhar; Jamil, Joheb Imtiaz (International Journal of Contemporary Pediatrics, 2026)
Background: Edematous malnutrition, a severe and acute malnutrition, still remains one of the main causes of morbidity and mortality among children under five years of age, particularly in low- and middle-income countries. Edematous malnutrition in children is usually combined with fluid retention and electrolyte disturbance that, if not treated early, can lead to life-threatening complications. The purpose of this study is to evaluate the trend and magnitude of serum electrolyte level and their association with edema severity in children with edematous malnutrition. Methods: It was a cross-sectional study conducted in the Department of Paediatrics Inpatient, Institute of Child and Mother Health (ICMH), Dhaka, Bangladesh from July 2019 to June 2020. There were 51 children aged between 6 months to 5 years with edematous malnutrition who were included via purposive sampling. Data were cleaned and analyzed using SPSS (version 20). Results: In the current study, most of the children were severely underweight (78.4%) and nearly half (47.1%) were severely stunted, while 31.4% were severely wasted. Mild oedema was detected in 51% of the children, followed by moderate (27.4%), and severe oedema (21.6%). The mean serum sodium, potassium, and chloride were 139.39±4.23 mEq/l, 4.24±0.59 mmol/l, and 105.09±3.27 mEq/l, respectively. A significant association was found between serum sodium levels and the severity of oedema, with children having severe oedema showing significantly lower mean sodium levels compared to those with mild oedema (p=0.036). Conclusions: This study demonstrates that among children with edematous malnutrition, serum sodium level showed a significant association with the severity of edema, with markedly lower sodium values observed in those with severe edema. In contrast, serum potassium and chloride levels did not vary significantly across different grades of edema.